Polymer‐based solid acid catalyst for the green production of diosgenin. Issue 6 (13th September 2021) - Yuan, Hui; Yu, Xuejun; Jiang, Wenxiu; Shen, Bowei; Zhang, Farong; Pan, Zhiquan; Zhou, Hong
Abstract: In this study, a novel polymer‐based solid acid catalyst was prepared by free radical polymerization of N, N′‐methylenebisacrylamide (MBA) and allyl sodium sulfonate (SAS), followed by acidifying of diluted hydrochloric acid. The prepared solid acid was fully characterized by FTIR, solid‐state 13 C‐NMR, TGA, XPS, element analysis, and SEM. In addition, the prepared solid acid poly(MBA‐SAA) was used as a catalyst to extract diosgenin from Dioscorea zingiberensis C.H.Wright (DZW) under solvethermal condition using ethanol as a solvent. And the optimal conditions of temperature (104.02°C), alcoholysis time (5.87 h) and solid acid dosage (0.39 g), were obtained by response surface analysis based on the results of single factor experiments. The yield of diosgenin (14.53%) obtained in the alcoholysis is higher than that of the traditional sulfuric acid hydrolysis method. The alcoholysis products were analyzed by high performance liquid chromatography‐mass spectrometry (LC–MS) and UV–vis, respectively. The results showed that the solid acid with higher catalytic activity and good reusability can replace sulfuric acid to extract diosgenin, which has a great potential for the clean production of diosgenin in industry. Abstract : A polymer‐based solid acid, poly(MBA‐SAA), with higher acidity was obtained, which exhibited good catalytic activity toward the extraction of diosgenin from dioscin